(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Cardiovascular disease (CVD) is the primary cause of disability and morbidity in many developed countries around the world. But timely management with cardiac surgery can reduce the mortality. Objectives: To assess the health related quality of life (HRQOL) of the CVD patients after coronary artery bypass grafting (CABG). Materials and Methods: This cross-sectional observational study was carried out among purposively selected CABG patients from January to December 2013. A total of 78 post CABG patients were interviewed with short form health survey (SF-36) questionnaire at different hospitals in Dhaka. Results: The study patients age ranged from 40 to 82 years and the proportion were higher among those of more than 60 years (38.5%) of age. Majority (48.7%) were educated up to HSC level. Explaining the characteristics of illness, the average duration of sufferings was 121.91±115.31 days and Post treatment duration in month was 14.97±19.25. The study findings showed a good level of QOL; with an average score of 78.2. The mental and physical components scores were 79.9 & 77.1 respectively. There were statistically significant (p<0.001) negative association between age and total component of quality of life of patients. In relation with sex, average total quality of life scores of male and female were 80.5±10.5 and 74.4±14 respectively which was statistically significant (p<0.001). Similarly, comparing to pre-treatment state, statistically significant (p<0.001) difference was found between groups quality of life. Similarly statistically significant difference was found with occupation in relation to total quality of life (p<0.001), physical component (p<0.01) and with mental component (p<0.05) of participants. Conclusion: Subjective perceptions of physical and psychological well-being changed significantly from before treatment to at least 3 months after treatment and better HRQOL noticed to the patients treated with CABG. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 50-53